Catecholamine metabolism via monoamine oxidase (MAO) within myocardium of individuals with type 2 diabetes - Nelson, Margaret A. M. (East Carolina University, 2019)
The primary comorbidity and cause of mortality in type 2 diabetes is cardiovascular disease. The structural and the functional cardiac remodeling observed in patients with type 2 diabetes has been shown to be driven by a plethora of mechanisms including mitochondrial dysfunction and oxidative stress. Monoamine oxidase (MAO), an enzyme located on the outer mitochondrial membrane, catabolizes catecholamines to produce two reactive byproducts upon substrate deamination: catechol-aldehyde and H2O2. We hypothesized that within environments of decreased redox buffering capacity like type 2 diabetes, these byproducts of MAO metabolism disrupt mitochondrial respiration and further drive redox imbalance. Furthermore, we hypothesized that the antioxidant and aldehyde scavenging capacity of carnosine could mitigate the reactivity of MAO-derived byproducts. A comprehensive analysis of catecholamine metabolism was performed in atrial myocardium from individuals with and without type 2 diabetes. MAO-A and-B maximal activity and expression were significantly increased within myocardium from individuals with diabetes and correlated with BMI. MAO-dependent metabolism of norepinephrine decreased ATP production within myocardium from individuals with type 2 diabetes. In addition, decreased aldehyde dehydrogenase and increased basal levels of catechol-protein adducts were observed within this metabolic group. Metabolomic analysis of atrial tissue from individuals with diabetes showed decreased catecholamine levels in the myocardium, supporting an increased flux through MAOs. As a proof of concept of our second hypothesis we showed that carnosine was able to sequester DOPAL, the dopamine-derived catecholaldehyde. Carnosine also attenuated DOPAL-dependent decrease in state 3 respiration in permeabilized fibers isolated from atria. Furthermore, the production of catechol-modified proteins was mitigated by carnosine in a concentration dependent manner. In conclusion, these findings illustrate a pathogenic mechanism for MAO within type 2 diabetes, and suggest that MAO-derived byproducts, especially catecholaldehydes, contribute to redox imbalance and altered mitochondrial bioenergetics observed in myocardium of individuals with type 2 diabetes. In addition, this translational study provides a mechanistic framework for the study of carnosine or related aldehyde scavengers as therapeutic approach for the prevention of cardiac dysfunction in patients with type 2 diabetes.
Keywords: Diabetes Mellitus, Type 2; Monoamine Oxidase; Myocardium; Biochemical Phenomena; Catecholamines